Pengaruh Rekrutmen, Pelatihan Kerja, Kompensasi dan Budaya Organisasi terhadap Kinerja Karyawan pada Bank Sumsel Babel Cabang Palembang - Hermawan, Iwan; Idris, Muhammad; Choiriyah, Choiriyah (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The purpose this study to determine the effect of recruitment, job training, compensation and organizational culture on employee performance of Bank Sumsel Babel Palembang branch. In this research, using associative research method with a population of 102 employees, the sampling technique is random sampling using the Issac and Michael formulas obtained by 74 employee respondents. The analysis technique uses the Instrument Test with Validity and Reliable Test, Classical Assumption Test and Multiple Linear Regression with the help of the SPSS 25 program. Based on the results of the study known that Recruitment has no significant effect on Employee Performance, Training, Compensation and Organizational Culture have a significant effect on Employee Performance partially while the variables Recruitment, Job Training, Compensation and Organizational Culture can explain the dependent variable